The Role of Demography in Moderation the Influence of Nonverbal Communication to Patient’s Satisfaction - Sudirman, Indrianty; Pasinringi, Syahrir A; Sidin, Indahwaty (International Journal of Medical and Health Sciences Research, 2016)
Effective nonverbal communication affects patient satisfaction and also affects the optimal level of patient’s healthiness. This is primarily caused by asymmetry information between doctor and patient since in most cases patients heavily rely on nonverbal communication as a tool to get information they need. Patient’s sensitivity to the nonverbal communication is generally varied in according to their demography characteristics. This research is aimed at analyzing the effect of non-verbal communication to the patient satisfaction with respect to different demographic perspectives. The research was carried out in the inpatient of selected hospitals in the Makassar city of Indonesia involving 420 respondents taken using proportional stratified random sampling technique. The research design is quantitative research using a cross sectional study design with questionnaires as the instrument to collect the data. The result of the study showed that the sixth variables of nonverbal communication (artifact, haptic, kinesics, chronemics, proxemics, and vocalic) significantly influence patient’s satisfaction. However, the result of the partial test showed different effects of each nonverbal communication variable to the patients based on the age categorize, gender, ward, ethnics, education level, and occupation.